Creative Clusters in Visegrad Countries: Factors Conditioning Cluster Establishment and Development - Bialic-Davendra Magdalena; Bednář Pavel; Danko Lukáš; Matošková Jana (Bulletin of Geography. Socio-Economic Series)
Since the accession of the Visegrad Group of countries (V4) to the European Union, the importance of clusters has increased. With growing global competitiveness and EU 12 trends, a gradual awareness of creative industries is observed in V4 countries. Therefore, this article analyses creative clusters and factors conditioning their establishment and development. On the basis of a literature review and a questionnaire survey, a mapping of creative clusters was conducted. In addition, catalysts, main motives and key factors in the process of their establishment were identified, as were the activities and factors hampering their development. The scheme of cluster development is presented as the outcome of the qualitative analysis, along with a comparison to findings of other studies. Research findings show that trust building and administrative obstacles are among the main barriers, especially for design clusters and cultural clusters.